Resources of educator’s professional activity - Dolinin E. V., Mukasheva N. S. (Interactive science, 2016)
the article deals with the idea of resource dependencies on the professional activity of teacher psychological prevention and stress tolerance as a personal quality of resistance to stress. the phenomenon of teacher profession, internal and external resources of professional work, levels, scientific and methodological recommendations are characterized.
Keywords: стрессоустойчивость; синдром профессионального выгорания; мобилизация личностных ресурсов; стресс-толерантность личности; психологическая профилактика; personal resources mobilization; stress resistance; professional burnout syndrome; psychological prevention; ресурсы профессиональной деятельности; внутренние ресурсы; внешние ресурсы; professional activity resources; internal resources; external resources; individual’s stress tolerance